Unlocking public health competencies: the dose–response effect of problem-based learning on undergraduate student outcomes - Falcon, Ashley; Porter, Andrew; Matsuda, Yui; Foronda, Cynthia L.; Lovan, Padideh; Graefe, Beck (Frontiers in Public Health, 2025)
IntroductionProblem-based learning (PBL) is a student-centered pedagogical strategy that emphasizes active learning through the exploration of complex real-world problems. While it has demonstrated effectiveness in undergraduate- and graduate-level programs, there is a notable gap in research on the dose–response relationship between the extent of PBL exposure and competency development in public health education. This study examines the effect of PBL on undergraduate public health students’ learning outcomes and explores the dose–response relationship between the extent of PBL exposure and the development of specific public health competencies in students.MethodsA pre-posttest design using surveys evaluated the impact of PBL across three undergraduate public health courses at a medium-sized, private university in South Florida. Students (n = 150) completed surveys at the beginning and end of each course to assess changes in 10 skill domains. Composite scores were calculated for each domain and overall competency. Repeated samples t-tests assessed pre-to-post course improvements, and linear regression analyses examined the dose–response effect of the number of PBL courses taken on competency development. Post-hoc analyses examined gender and racial/ethnic differences.ResultsSignificant increases were found across all 10 learners’ skill domains from pre- to post-course measurements, with the most substantial gains in Data Literacy (Cohen’s d = 0.812), Critical Thinking (Cohen’s d = 0.726), and Public Speaking (Cohen’s d = 0.672). The number of PBL courses taken significantly predicted the total skill competency score (β = 0.24, p = 0.02), indicating a dose–response effect. Significant relationships were also found for individual domains such as Critical Thinking (β = 0.27, p = 0.009), Data Literacy (β = 0.24, p = 0.02), and Team Dynamics (β = 0.25, p = 0.02).ConclusionFindings demonstrate that PBL effectively enhances several competencies critical to public health practice among undergraduate students. The novel discovery of a dose–response relationship suggests that increased exposure to PBL may lead to cumulative improvements in competencies. These results support the integration of multiple PBL courses in undergraduate public health curricula.